THE AQUARES MODEL: DOES IT HAVE IMPACT ON IMPROVING PERSONAL AND SOCIAL RESPONSIBILITY? - Ermawan Susanto; Pamuji Sukoco; Suharjana Suharjana (Jurnal Cakrawala Pendidikan, 2020)
Accidents in swimming pools which involve drowning are more likely to happen in Indonesia. Cases of accidents in swimming pools might indicate that there may be lack of  responsibility among the swimmers. Therefore, there is a need to improve this condition. The purpose of this study was to determine the impact of the Aquares model developed from Teaching Personal and Social Responsibility (TPSR) theory, on the students’ responsibility in swimming lessons. This study used an experimental method with one group pretest-posttest design. The study population was students of grade four with a sample of 60 students taken through cluster random sampling. The Tool for Assessing Responsibility-Based Education (TARE) was the instrument used to measure personal and social responsibility. The paired sample t-test analysis showed that there is a significant impact of the Aquares model on the increase of the students’ personal and social responsibility. Aspect of the increased responsibility include: respect, participation, self-direction, caring, and role model. The Aquares model applied in this study provides a strong framework for creating a meaningful and responsible environment for learning.